1993
DOI: 10.1021/jf00034a043
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine interactions with clay minerals: Kinetics and equilibria of sorption

Abstract: A novel technique using on-line microfiltration and HPLC analysis has been used to study sorption kinetics and sorption equilibrium of the herbicide atrazine with the clay minerals montmorillonite, kaolinite, and illite and the clay fraction of a soil. Fast and slow labile sorption have been observed for atrazine along with a reversible but kinetically slow sorption/desorption process that is consistent with diffusion of pesticide into the interior of the clay particles. Labile sorption capacity, mole fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
2
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 21 publications
5
62
2
1
Order By: Relevance
“…Complete reversibility of atrazine sorption by a number of Ca-saturated smectites at pH ranging from 4.75 to 6.45 (Laird et al 1992) support the above inference. Reversible sorption of atrazine by Na-and Ca-saturated montmorillonite, kaolinite and illite clay slurries at pH 5.1 has also been observed by Gilchrist et al (1993). The absence of any dealkylated or hydrolyzed atrazine species even after the 127-d reaction period (Gilchrist et al 1993) further corroborates the conclusion that atrazine is sorbed as neutral molecules by the homoionic smectite samples used here.…”
Section: Methodssupporting
confidence: 81%
“…Complete reversibility of atrazine sorption by a number of Ca-saturated smectites at pH ranging from 4.75 to 6.45 (Laird et al 1992) support the above inference. Reversible sorption of atrazine by Na-and Ca-saturated montmorillonite, kaolinite and illite clay slurries at pH 5.1 has also been observed by Gilchrist et al (1993). The absence of any dealkylated or hydrolyzed atrazine species even after the 127-d reaction period (Gilchrist et al 1993) further corroborates the conclusion that atrazine is sorbed as neutral molecules by the homoionic smectite samples used here.…”
Section: Methodssupporting
confidence: 81%
“…The role of minerals on atrazine adsorption in soil is not well documented. Gilchrist et al (1993) found that the adsorption capacity of clays for atrazine followed the order of montmorillonite > illite > kaolinite.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of clay minerals to the adsorption of organic molecules in soil has been the object of several studies (e.g., Mortland 1970, 1976, Pusino et al 1991, Laird et al 1992, Gilchrist et al 1993, Weber 1993. Of the various soil clay constituents, smectites have the greatest potential for adsorption of pesticides due to their large surface area and abundance in agricultural soils (Laird et al 1992).…”
Section: Introductionmentioning
confidence: 99%